Impact of Online gaming on Academic Performance of Pokhara University Business Students in Kathmandu Valley - Shahi, Siddhant Bikram; Saud, Santosh (Nepalese Journal of Management, 2024)
This study examines the impact of online gaming on the academic performance of Pokhara university business students in Kathmandu Valley. Academic performance of business students is the dependent variable. The selected independent variables are online games, social media network, time spent on social media, mobile phones, friends and people connection and internet addictions. The primary source of data is used to assess the opinions of the respondents regarding the impact of online gaming on academic performance of Pokhara university business students in Kathmandu Valley. The study is based on primary data with 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of online gaming on academic performance of Pokhara university business students in Kathmandu Valley. The study showed that online gaming has a positive impact on academic performance of business student indicating that playing informative online gaming leads to increase in the level of academic performance of business students. Likewise, the result also revealed that social media network has a positive impact on academic performance of business students. It means that use social media network helps in improving student’s academic performance. Moreover, time spent on social media has a positive impact on academic performance of business students indicating that more the time students spent on social media for the purpose, better would be the academic performance of the students. Moreover, mobile phones has a positive impact on academic performance of business students. It indicates that use of mobile phones helps in improving academic performance of business students. Further, the result shows that friends and people connection has a positive impact on academic performance of business students which means that connecting with friends and people through social media helps students to improve their academic performance.